Experimental Investigation of the Effects of Process Parameters on Cutting Force in External Cylindrical Grinding - T.-L. Nguyen; V.T. Thai; L. Hoang (Tribology in Industry, 2021)
Cutting force is a vital parameter that affects product quality. Proper control of the cutting force helps optimize the production process as it improves productivity and product quality. This paper assesses the influence of machining parameters, such as alloy steel hardness and workpiece diameters, to cutting forces when external cylindrical grinding by experimental methods. The cutting force was measured using a workpiece shaft-mounted sensor with a balanced bridge-type resistor sensor. Steel for testing: 40Cr, 9CrSi, 65Mn, and W18Cr4V, which were heat-treated at three different hardness levels: 40, 50, and 60 HRC. The Taguchi method's experimental results show that the main parameters affecting cutting forces are: Feed rate of the grinding wheel Sd, cutting depth t, and hardness of workpiece material on the HRC scale. Since then, we built a mathematical model of the normal cutting force function Fn and tangent cutting force function Ft according to Sd, t, and HRC of 9CrSi steel then tested again with three steel types: 40Cr, 65Mn, and W18Cr4V for quite similar results. The cutting force is controlled through cutting parameters suitable for different hardness and workpiece material based on this model.